Analgesic treatment in acute pain of odontogenic origin - Bogdan Pricop; Cristina Nistor; Irina Gheorghiu; Paula Perlea (Amaltea Medical Publishing House, 2023)
Pain is one of the main reason that compels patients to visit dentists. Poorly managed pain following treatment in the dental office can lead to patients lack of trust in the dentist, postponing or even avoiding dental treatments. The physiopathology of pain is a complex process involving both the central nervous system and the peripheral nervous system, so the use of analgesics with different modes of action can lead to improved, faster and longer-lasting pain relief. This article provides an overview of the mode of action, effectiveness and results obtained from studies in the literature related to the combination of ibuprofen and paracetamol in a single tablet.